Foreign direct investment and its impact on CO2 emissions at various levels of economic development - Abdullahi, Abubakar; Ibrahim, Saifuzzaman; W.N.W, Azman-Saini; Law, Siong Hook (UPM Press, 2023)
Foreign direct investment (FDI) may have a negative impact on carbon dioxide (CO2) emissions through imported technologies that cause air pollution. However, previous studies presented inconclusive results on the impact of FDI on CO2 emissions. This indicates the possibility of other factors or different economic conditions that can explain the observed contradicting impacts of FDI on CO2 emissions. This study examines the impact of FDI on CO2 emissions at various levels of economic development. In a sample of 123 countries, results from the bias-corrected least-squares dummy variable (LSDVC) technique show that FDI asymmetrically affects CO2 emissions. The presence of FDI lowers CO2 emissions in countries with higher incomes and raises carbon emissions in countries with lower incomes. This finding also suggests that FDI inflows introduce greener technologies in high and middle-income countries. Meanwhile, dirty FDI flows into low-income countries and adversely affects the environment.